The propagation of seismic waves, misinformation, and disinformation from the 2024-10-05 M 4.5 Iran earthquake - Benjamin Fernando; Ross Maguire; Brianna Fernandez; Saman Karimi; Elizabeth Koenck; Göran Ekström; Tom Rivlin; Celeste Labedz (Seismica)
The 2024-10-05 Iran M 4.5 earthquake took place at a time of heightened tensions in the Middle East. We perform a discrimination and moment tensor analysis and identify a shallow-dipping, reverse fault source commensurate with the compressional setting of the Iranian interior. Nonetheless, the event's aftermath saw widespread dissemination of misinformation, and potentially active disinformation, concluding that it was in fact a test of an Iranian nuclear weapon. The `evidence' for many of these claims was based on inaccurate interpretation of seismic data. In this paper, we analyse how geophysical `fake news' propagated through social media (mainly Twitter/X) following this event, eventually gaining traction in mainstream, earned media. This event is an illustrative warning of how seismic data can be misinterpreted and/or manipulated in public discourse.